2020
DOI: 10.1097/phm.0000000000001596
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise After Left-Sided Stroke Improves Gait Speed and Endurance

Abstract: Objective The aim of the study was to investigate the effects of aerobic exercise on individuals who have had a stroke and showed baseline scores lower than the standard scores for the 6-min and 10-meter walk tests. Design Individuals were assigned to groups according to gait performance, defined by the standard values in the 6-min and 10-meter walk tests (standard baseline score and lower baseline score), and brain injury side. Aerobic exercise, 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We conducted 18 training sessions of high intensity gait training using a soft exosuit on five individuals in the chronic phase of post-stroke recovery. The main clinical outcomes of the intervention were improving walking speed and endurance as they are the primary walking goals of the physical therapy intervention after stroke [ 18 , 19 ]. The secondary outcomes were the gait quality measures including spatiotemporal characteristics and joint kinematics to evaluate changes in gait impairments throughout the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted 18 training sessions of high intensity gait training using a soft exosuit on five individuals in the chronic phase of post-stroke recovery. The main clinical outcomes of the intervention were improving walking speed and endurance as they are the primary walking goals of the physical therapy intervention after stroke [ 18 , 19 ]. The secondary outcomes were the gait quality measures including spatiotemporal characteristics and joint kinematics to evaluate changes in gait impairments throughout the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that walking speed and endurance are closely associated with the level of functional independence (27,28) and are the primary goals of rehabilitation intervention after stroke (29,30). Secondary outcome measures included the FAC, Berg Balance Scale (BBS), and Fugl-Meyer Assessment for lower limb subscale (FAM-LE).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…We combine the method of symmetric matrix fusion tracking and recognition to obtain the pixel distribution matrix element (h ij ) of the basketball training pose image. 4 Under the three-dimensional visual tracking recognition model, we construct a fuzzy parameter recognition model of basketball training pose motion images. Assume that the cluster center grid parameter distributions for motion-imaging are a, b, c and γ, θ and ꞷ.…”
Section: Methods Experimental Subjectsmentioning
confidence: 99%